Jejunojejunal intussusception secondary to inflammatory fibroid polyp: A rare cause of small bowel obstruction - Jun Sam Tan; Kai Ming Teah; Vee Chuan Hoe; Allim Khairuddin; Harivinthan Sellapan; Firdaus Hayati; Nor Haizura Ab Rani (Elsevier, 2020)
Background: Adult intussusception is a relatively rare clinical entity. The majority of cases of intussusception in adults are due to a pathologic condition that serves as a lead point and requires surgery. Small bowel intussusception is usually caused by benign or malignant neoplasms appearing at the head of the invagination. Inflammatory fibroid polyp (IFP) of the small bowel is an unusual benign neoplastic lesion that has been rarely reported to cause intussusception, especially in the jejunum. Case presentation: We present a rare case of adult intussusception who presented with a triad of intestinal obstruction. Computed tomography revealed small bowel intussusception with bowel ischemia. Intraoperatively, she required resection of the small bowel and primary anastomosis. Macroscopic examination revealed a single pedunculated polyp, which is the lead point of intestinal obstruction and confirmed histologically. Conclusion: Inflammatory fibroid polyp should be considered as a cause of intussusception among adults with small bowel obstruction.